The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1521/aeap.2010.22.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Project Roadmap: Reeducating Older Adults in Maintaining AIDS Prevention: A Secondary Intervention for Older HIV-Positive Adults

Abstract: The number of older adults living with HIV/AIDS is larger than ever. Little is known about their sexual behaviors, although contrary to stereotypes, older adults desire and engage in sexual activity. Despite increased recognition of the need for prevention interventions targeting HIV-positive individuals, no secondary HIV prevention interventions have specifically targeted the older HIV-positive adult. Efforts to target high-risk sexual behaviors may be even more critical in the older population because of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 19 publications
2
68
0
Order By: Relevance
“…Consistent with current research (Illa et al, 2010;Schick et al, 2010), the findings provide additional evidence that the population of older adults needs to be taken seriously as being at risk because of past, current, and future sexual activity. The authors believe that findings from these focus groups indicate that older adults may in fact see the importance of HIV/AIDS awareness, but that ageist stereotypes held by such external sources as their doctors and other healthcare providers may be contributing to the belief that HIV/AIDS prevention education is not necessary for this population.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with current research (Illa et al, 2010;Schick et al, 2010), the findings provide additional evidence that the population of older adults needs to be taken seriously as being at risk because of past, current, and future sexual activity. The authors believe that findings from these focus groups indicate that older adults may in fact see the importance of HIV/AIDS awareness, but that ageist stereotypes held by such external sources as their doctors and other healthcare providers may be contributing to the belief that HIV/AIDS prevention education is not necessary for this population.…”
Section: Discussionsupporting
confidence: 84%
“…The four articles conducted among HIV-negative participants aimed to improve general HIV knowledge to facilitate HIV prevention. Within the studies among HIV-positive participants, the main outcome measure of Lovejoy and colleagues [53] and Illa and colleagues [54] articles was reduced sexual risk behavior. The three Heckman et al articles [35,37,55] focused on mental health and coping assessments while the two Souza et al papers [36,56] emphasized physical status and strength.…”
Section: Resultsmentioning
confidence: 99%
“…A summary score on the outcome variable 'General knowledge of HIV' was obtained by summing the item scores, 1 = yes and was rated as very high for a score of 4 points (that is 'yes' on all items), high for a score of 3 points ('yes' on any 3 items), medium for 2 points and low for a score of 1 point. 20 The results show that 95.7% (n = 580) of the older adults have very high knowledge of HIV and AIDS, 4.1% (n = 25) have high knowledge while 0.2% (n = 1) have low knowledge.…”
Section: General Knowledge Of Hiv and Aidsmentioning
confidence: 94%
“…studies that report continued high rates of unprotected intercourse among people with HIV, approximating 33%. 20,32,33 The authors showed that interventions to reduce risk of HIV transmission resulted in significantly less unprotected intercourse and greater condom use at follow-up. Transmissionrisk behaviours with non-HIV-positive sexual partners and estimated HIV transmission rates over a one-year horizon were also significantly lower for the behavioural risk-reduction intervention group.…”
Section: Knowledge Of Risks Associated With Hiv Infectionmentioning
confidence: 99%